Multinationals and U.S. Productivity Leadership Evidence from Great Britain - Criscuolo, Chiara (OECD Science, Technology and Industry Working Papers, 2004)
US plant level studies show US multinational enterprises (MNE) are more productive than other MNEs. This could reflect US productivity leadership or could be due to the ease in which US firms operate in their home surroundings. The evidence would therefore be more compelling if US firms were leaders outside the US. We study the productivity of plants owned by US firms located in the UK. Our study differs from many studies of foreign owned plants in three ways. Firstly, using a newly available dataset we can identify not only foreign but also domestic MNEs. We find that UK MNEs are less productive than US owned plants, but as productive as non US foreign owned plants. Secondly, having a panel dataset we distinguish between different hypotheses regarding the nature of the US and MNE advantage. We find strong evidence that the US advantage lies in the ability to takeover already productive plants. Whereas we find some evidence for a shared asset effect for MNEs in general we do not find any evidence that the US advantage is driven by superior shares assets. Thirdly, this paper features a novel approach to TFP calculation